HER2-Altered Non-Small Cell Lung Cancer: Biology, Clinicopathologic Features, and Emerging Therapies - Yu, Xin; Ji, Xianxiu; Su, Chunxia (Frontiers in Oncology, 2022)
Multiple oncogenic molecular alterations have been discovered that serve as potential drug targets in non-small cell lung cancer (NSCLC). While the pathogenic and pharmacological characteristics of common targets in NSCLC have been widely investigated, those of uncommon targets are still needed to be elucidated. Human epidermal growth factor receptor 2 (HER2, ERBB2)-altered tumors represent a highly heterogeneous group of diseases, which consists of three distinct situations including mutation, amplification and overexpression. Compared with breast and gastric cancer, previous studies have shown modest and variable results of anti-HER2 treatments in lung cancers with HER2 aberrations, thus effective therapies in these patients remain an unmet medical need. By far, promising efforts to novel treatment strategies have been made to improve the clinical outcomes of these patients. In this review, we describe the molecular and clinicopathologic features of HER2 alterations and systematically summarize recent studies on emerging therapies for this subset of patients.